2000
DOI: 10.1046/j.1523-1747.2000.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergens and Irritants Transcriptionally Upregulate CD80 Gene Expression in Human Keratinocytes

Abstract: The human CD80 costimulatory molecule is an important signal between professional antigen-presenting cells and T helper cells. The immunobiology of CD80 expression by keratinocytes, especially during allergic and irritant contact dermatitis, however, is less well understood. CD80 cell surface expression and gene transcription by keratinocytes was increased when keratinocytes were exposed to certain allergens (chemicals that induce inflammation via hapten-specific T cells) and irritants (chemicals that are toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 54 publications
1
30
1
Order By: Relevance
“…Expression of HLA class I was further up-regulated, raising the possibility that IFN-c may also promote increased presentation of antigen to CD8 + T cells. Previous studies have suggested that CD80 gene expression may be upregulated by allergen or inflammatory mediators [17,18]. However, we did not observe change in CD80 or CD86 expression following incubation with IFN-c staphylococcal enterotoxin B, LPS, corticosteroids, IL-2, IL-4, IL-5, IL-10 or IL-13 ( Fig.…”
Section: Resultscontrasting
confidence: 47%
“…Expression of HLA class I was further up-regulated, raising the possibility that IFN-c may also promote increased presentation of antigen to CD8 + T cells. Previous studies have suggested that CD80 gene expression may be upregulated by allergen or inflammatory mediators [17,18]. However, we did not observe change in CD80 or CD86 expression following incubation with IFN-c staphylococcal enterotoxin B, LPS, corticosteroids, IL-2, IL-4, IL-5, IL-10 or IL-13 ( Fig.…”
Section: Resultscontrasting
confidence: 47%
“…In human keratinocytes, B7-1 gene expression is induced by allergens and irritants (16). In P815 mastocytoma tumor cells, B7-1 gene expression is induced by oxidative stress (17).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about B7-1 expression by non-bone marrow-derived cells. In human keratinocytes, B7-1 gene expression is upregulated by allergens and irritants (16). In P815 mastocytoma tumor cells, B7-1 gene expression is induced by oxidative stress (17), which is reminiscent of the induction of B7-1 in podocytes by puromycin, described below.…”
Section: Introductionmentioning
confidence: 99%
“…For example, triggering of B7-1 blocks B cell proliferation and Ab production (55). Other examples include the induction of B7-1 in kidney podocytes, resulting in an increase in glomerular filtration and transient proteinuria (56) and the induction of B7-1 expression on keratinocytes by inflammatory stimuli (57). Therefore, the function of costimulatory molecules extends beyond their traditional role in T cell signaling and may explain the broader expression pattern of these molecules on cell types other than APC (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%